Temperature‐Activated Reverse Sensing Behavior of Pd Nanowire Hydrogen Sensors. Issue 2 (10th September 2012) - Yang, Dachi; Valentín, Luis; Carpena, Jennifer; Otaño, Wilfredo; Resto, Oscar; Fonseca, Luis F.
<x xml:space="preserve">Abstract</x> Hydrogen sensors built with individual palladium nanowires (Pd NWs) have been achieved by integrating Pd NWs across microelectromechanical system (MEMS) electrodes, followed by assembling and bonding them to a chip carrier platform. The sensing measurements reveal that the sensors with individual Pd NWs show reverse sensing behaviors between the temperature zones of (370–263 K) and (263–120 K). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>